The near-infrared bacteriophytochrome-derived fluorescent protein PENELOPE enables RESOLFT superresolution microscopy - Daniel Stumpf; Nickels Jensen; Cédric Mittelheisser; Jan Keller-Findeisen; Alexey I. Chizhik; Maria Kamper; Timo Diekmann; Florian Habenstein; Isabelle Jansen; Jörg Enderlein; Michel Sliwa; Kaushik Inamdar; et al. (Proceedings of the National Academy of Sciences, 2025)
REversible Saturable Optical Linear Fluorescence Transitions (RESOLFT) superresolution microscopy fundamentally overcomes the diffraction barrier in far-field fluorescence microscopy. It relies on reversibly switchable fluorescent proteins (RSFPs) that allow repeated light-induced transitions between fluorescent on- and nonfluorescent off-states. Because these transitions are induced by low-light intensities, RESOLFT superresolution microscopy is particularly suitable for live-cell imaging. So far, RESOLFT imaging has only been performed in the visible range of the electromagnetic spectrum. To expand the RESOLFT concept into the near-infrared (NIR) region, which is characterized by reduced autofluorescence, lower scattering and decreased phototoxicity, we developed the p hotostabl e N IR r e versibly switchab l e flu o rescent p rot e in (PENELOPE), which is the first RSFP applicable in the NIR window. PENELOPE was generated by mutagenesis of the chromophore-binding domain of the Deinococcus radiodurans bacteriophytochrome. This NIR-RSFP exhibits high photostability and high ensemble switching contrast at low-light intensities. It also undergoes an unusually fast thermal fluorescence recovery from the dark state into an on-state. This was exploited for low-light intensity RESOLFT imaging with only a single wavelength, as the same light wavelength (660 nm) is used for off-switching and fluorescence readout, while the on-switching occurs in the absence of illumination. We demonstrate RESOLFT recordings both in chemically fixed and in living human cells using PENELOPE as a fusion protein.